2022
DOI: 10.1155/2022/3595033
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture as Treatment for Female Infertility: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background. The effects of acupuncture on female infertility remain controversial. Also, the variation in the participant, interventions, outcomes studied, and trial design may relate to the efficacy of adjuvant acupuncture. The aim of the study is to systematically evaluate the efficacy and safety of acupuncture for female with infertility and hopefully provide reliable guidance for clinicians and patients. Methods. We searched digital databases for relevant studies, including EMBASE, PubMed, Cochrane Library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Another trial conducted a year later found that patients who received placebo acupuncture intervention had more ongoing pregnancy and implantation rates than those who discontinued the trial ( 29 ) . Another recent meta-analysis, Quan et al ( 31 ) in 2022 agreed with our findings of a benefit to acupuncture in their analysis of 27 studies. Their analysis included studies from worldwide without a specific subgroup analysis.…”
Section: Discussionsupporting
confidence: 87%
“…Another trial conducted a year later found that patients who received placebo acupuncture intervention had more ongoing pregnancy and implantation rates than those who discontinued the trial ( 29 ) . Another recent meta-analysis, Quan et al ( 31 ) in 2022 agreed with our findings of a benefit to acupuncture in their analysis of 27 studies. Their analysis included studies from worldwide without a specific subgroup analysis.…”
Section: Discussionsupporting
confidence: 87%
“…Non-medical endometriosis treatments include antioxidants [ 21 ], Chinese herbal medicines [ 22 , 23 ], acupuncture [ 24 ], reflexology, homeopathy, psychotherapy, exercise and sports and nerve blocks such as a superior hypogastric plexus block [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang, included 27 studies containing 7676 subjects and found that acupuncture was effective in treating infertility, especially in ovulatory disorders and PCOS combined infertility [63]. Quan et al [64] also concluded that acupuncture or combined with other therapies significantly increased pregnancy and live birth rates in women with PCOS [64]. When acupuncture is applied to gynecological disorders, it can regulate the function of hypothalamic-pituitary-ovarian axis (HPOA), promote ovulation, and improve endometrial tolerance.…”
Section: Acupuncture For Pcos With Infertilitymentioning
confidence: 99%